Biofunctionalized and self-supported polypyrrole frameworks as nanostructured ECM-like biointerfaces. Issue 41 (22nd June 2018) - Lefèvre, Damien; Louvegny, Juliette; Naudin, Mathieu; Ferain, Etienne; Dupont-Gillain, Christine; Demoustier-Champagne, Sophie
Abstract : A versatile template-based approach allows for the synthesis of nanostructured biointerfaces, made of core–shell nanotubes, combining bioactivity and mechanical stability. Abstract : Hybrid nanobiointerfaces were designed as an original contribution to the challenge of synthesizing nanostructured biomaterials integrating a set of cell fate-determining cues, originally provided to cells by the extracellular matrix (ECM). The produced biointerfaces consist of a stiff framework of intersected polypyrrole (PPy) nanotubes supporting a soft multilayer composed of ECM-derived biomacromolecules: collagen (Col) and hyaluronic acid (HA). PPy frameworks with highly tunable characteristics were synthesized through chemical oxidative polymerization of pyrrole monomers, templated within track-etched polycarbonate (PC) membranes featuring a network of intersected nanopores. PPy interfaces with a porosity of 80%, composed of nanotubes with an average diameter ranging from 40 to 300 nm, intersecting at an angle of 90°, were shown to be self-supported. These rigid PPy nanostructured interfaces were functionalized with a self-assembling (HA/Col) multilayer deposited via a layer-by-layer process. Biofunctionalized and unmodified PPy frameworks were both shown to promote sustained cell adhesion, therefore demonstrating the cytocompatibility of the engineered matrices. Such nanobiointerfaces, combining a mechanically-stable framework of tunable dimensions with a soft biopolymeric multilayer of highly versatile nature, pave the way towards cell-instructive biomaterials able to gather a wide range of cues guiding cell behavior. The developed self-supported structures could be used as a coating or as membranes bridging different tissues.